Matthew 1-13 : New Testament 1a - Simonetti, Manlio (Downers Grove, Ill. : InterVarsity Press, 2001)
"The Ancient Christian Commentary on Scripture does what very few of today's students of the Bible could do for themselves. With the aid of computer technology, the vast array of writings from the church fathers - including much that is available only in the ancient languages - have been combed for their comment on Scripture. From these results, scholars with a deep knowledge of the fathers and a heart for the church have hand-selected material for each volume, shaping, annotating and introducing it to today's readers. Each portion of commentary has been chosen for its salient insight, its rhetorical power and its faithful representation of the consensual exegesis of the early church."--BOOK JACKET.
1. Matthew 1-13 -- 2. Matthew 1-28
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Matthew -- Commentaries